Biological Activities of Herbaceous Peony Flower Extracts - Jin, Ying-Shan; Xuan, Yong-Hao; Jin, Yin-Zhe; Chen, Man-Li; Tao, Jun (Asian Journal of Chemistry, 2013)
Herbaceous peony (Paeonia lactiflora Pall.) root is an important Traditional Chinese Medicine. To determine if the flower has any beneficial properties, we investigated antioxidant, antiinflammatory and anti a-glucosidase activities of petroleum ether, ethyl ether, ethyl acetate, n-butanol and water extracts of herbaceous peony flower. Antioxidant activity was evaluated by measuring total phenolic content, total antioxidant activity and DPPH radical scavenging activities. The ethyl ether and ethyl acetate extracts exhibited higher antioxidant ability than the other extracts. Moreover, the ethyl ether and ethyl acetate extracts had greater antiinflammatory activity on murine macrophage cells (RAW264.7). On the other hand, the petroleum ether extract and ethyl acetate extract showed strong inhibitory effect on a-glucosidase. These results suggest that flower from Herbaceous peony may have health-enhancing effects.